Identification of a Small‐Molecule Inhibitor of HIV‐1 Assembly that Targets the Phosphatidylinositol (4, 5)‐bisphosphate Binding Site of the HIV‐1 Matrix Protein. Issue 3 (29th January 2013) - Zentner, Isaac; Sierra, Luz‐Jeannette; Fraser, Ayesha K.; Maciunas, Lina; Mankowski, Marie K.; Vinnik, Andrei; Fedichev, Peter; Ptak, Roger G.; Martín‐García, Julio; Cocklin, Simon
Abstract The development of drug resistance remains a critical problem for current HIV‐1 antiviral therapies, creating a need for new inhibitors of HIV‐1 replication. We previously reported on a novel anti‐HIV‐1 compound, N2‐(phenoxyacetyl)‐N‐[4‐(1‐piperidinylcarbonyl)benzyl]glycinamide (14), that binds to the highly conserved phosphatidylinositol (4, 5)‐bisphosphate (PI(4, 5)P2) binding pocket of the HIV‐1 matrix (MA) protein. In this study, we re‐evaluate the hits from the virtual screen used to identify compound 14 and test them directly in an HIV‐1 replication assay using primary human peripheral blood mononuclear cells. This study resulted in the identification of three new compounds with antiviral activity; 2‐(4‐[3‐(4‐fluorophenyl)‐1, 2, 4‐oxadiazol‐5‐yl]methyl)‐1‐piperazinyl)‐N‐(4‐methylphenyl)acetamide (7), 3‐(2‐ethoxyphenyl)‐5‐[[4‐(4‐nitrophenyl)piperazin‐1‐yl]methyl]‐1, 2, 4‐oxadiazole (17), and N‐[4‐ethoxy‐3‐(1‐piperidinylsulfonyl)phenyl]‐2‐(imidazo[2, 1‐b][1, 3]thiazol‐6‐yl)acetamide (18), with compound 7 being the most potent of these hits. Mechanistic studies on 7 demonstrated that it directly interacts with and functions through HIV‐1 MA. In accordance with our drug target, compound 7 competes with PI(4, 5)P2 for MA binding and, as a result, diminishes the production of new virus. Mutation of residues within the PI(4, 5)P2 binding site of MA decreased the antiviral effect of compound 7. Additionally, compound 7 displays a broadly neutralizing anti‐HIV activity, with IC50 values of 7.5–15.6 μM for the group M isolates tested. Taken together, these results point towards a novel chemical probe that can be used to more closely study the biological role of MA and could, through further optimization, lead to a new class of anti‐HIV‐1 therapeutics.